Pengaruh Keseimbangan Kehidupan Kerja Terhadap Kepuasan Kerja Karyawan Pada Unit Shared Service PT. Telkom Regional VII Makassar - Idris, Abdi Akbar; Hasbiah, Siti (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The influence of globalization during the industrial revolution on companies has caused changes and competition has become increasingly competitive. Human resources are one of the most important factors in facing global competition, so it is necessary to pay attention to their quality. This study aims to determine the effect of work life balance as an aspect that needs to be considered by companies because it affects job satisfaction and employee performance. This research was conducted at the Shared Service Unit of PT. Telkom Regional VII Makassar with a total of 38 respondents. This research is a quantitative research with a descriptive approach and is a population study. This study analyzes the effect of work life balance on employee job satisfaction. The results of the study show that work life balance as a whole is included in the High category. This shows that the work life balance of employees at the Shared Service Unit of PT. Telkom Regional VII Makassar has been running well as expected by employees at the Shared Service Unit of PT. Telkom Regional VII Makassar. Meanwhile, based on the simple regression results, the variable shows an R value (correlation) of 0.317. The R Square value of 0.317 equals 31.7%, so it can be concluded that the work life balance variable (X) influences the job satisfaction variable (Y) by 31.7%.